Benign prostatic hyperplasia after prostatic arterial embolization in a canine model: A 3T multiparametric MRI and whole‐mount step‐section pathology correlated longitudinal study. Issue 4 (9th February 2017) - Li, Basen; Xu, Anhui; Wang, Nan; Min, Xiangde; Feng, Zhaoyan; Deng, Ming; Li, Liang; Cai, Jie; Kang, Zhen; Jiang, Kehua; Kuang, Dong; Wang, Liang
Abstract : Purpose: To explore the morphological and functional characteristics of prostatic arterial embolization (PAE) in a canine model of benign prostatic hyperplasia (BPH) with 3T multiparametric magnetic resonance imaging (mp‐MRI) and whole‐mount step‐section pathology correlation. Materials and Methods: Eight adult male beagle dogs with hormone‐induced BPH underwent 3T mp‐MRI before and 1, 3, and 6 months after PAE, with subsequent whole‐mount step‐section pathologic assessment. Images were acquired using T 1 ‐weighted images ( T 1 WI), T 2 WI, 3D‐SPACE, diffusion‐weighted imaging (DWI), susceptibility‐weighted imaging (SWI), T 2 ‐mapping, and dynamic contrast‐enhanced (DCE) sequences. Variance analysis was performed to assess statistical differences in prostatic volume (PV), apparent diffusion coefficient (ADC), and T 2 values. Pearson correlation analysis was performed to correlate ADC, T 2, and PV. Results: The PV decreased from baseline to 1, 3, and 6 months after PAE from (25.88 ± 7.09) cm 3 to (6.48 ± 2.08) cm 3, (6.48 ± 3.39) cm 3, (6.20 ± 2.88) cm 3 . The ADC values sequentially decreased from baseline to 1, 3, and 6 months after PAE from (1497.06 ± 222.72) × 10 −6 mm 2 /s to (1056.00 ± 189.46) × 10 −6 mm 2 /s, (950.48 ± 77.85) × 10 −6 mm 2 /s, (980.98 ± 107.78) × 10 −6 mm 2 /s. The T 2 values decreased from baseline to 1, 3, and 6 months after PAE were (83.74 ± 5.29) msec, (68.72 ± 5.66) msec, (53.96 ± 15.04) msec, (49.81 ± 13.34) msec, respectively. ADC and T 2 values were positively correlated with PV ( r = 0.823 and 0.744, respectively). Microhemorrhages and hemosiderin were found on SWI after PAE. Conclusion: 3T mp‐MRI may facilitate noninvasive assessment of morphological and functional changes of BPH after PAE. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1220–1229.